1986
DOI: 10.1104/pp.81.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Heat Inactivation of Starch Synthase in Wheat Endosperm Tissue

Abstract: ABSTRACIThe effect of temperature on accumulation of starch was studied in grain slices of wheat (Titicum aestivum cv SUN9E), taken 15 days after anthesis. As compared with pretreatment of such slices at 25°C, pretreatment at 30 or 35C reduced the subsequent conversion of sucrose to starch. In contrast to rice (Oryza sativa cv Calrose), pretreatment of wheat soluble starch synthase in vitro at 30°C or higher temperatures reduced its activity. In zymograms using nondenaturing polyacrylamide gel electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 17 publications
7
40
0
1
Order By: Relevance
“…These results are in line with previous reports (Piper and Boote 1999;Thomas et al 2003) in which the starch and soluble sugar contents in soybean seeds were found to decrease with rise in temperature. Similar correlations have been observed in other crops such as rice (Ahmed et al 2015) and wheat (Rijven 1986;Zhao et al 2006;Yan et al 2008;Liu et al 2011). The reasons for this phenomenon were supposedly the lower activities of starch synthase, ADP-glucose pyrophosphorylase, starch phosphorylase, and soluble starch synthase enzymes involved in sucrose to starch conversion at higher temperatures (Rijven 1986).…”
Section: Discussionsupporting
confidence: 59%
“…These results are in line with previous reports (Piper and Boote 1999;Thomas et al 2003) in which the starch and soluble sugar contents in soybean seeds were found to decrease with rise in temperature. Similar correlations have been observed in other crops such as rice (Ahmed et al 2015) and wheat (Rijven 1986;Zhao et al 2006;Yan et al 2008;Liu et al 2011). The reasons for this phenomenon were supposedly the lower activities of starch synthase, ADP-glucose pyrophosphorylase, starch phosphorylase, and soluble starch synthase enzymes involved in sucrose to starch conversion at higher temperatures (Rijven 1986).…”
Section: Discussionsupporting
confidence: 59%
“…such as insensitive response of starch synthase in rice endosperm to high temperature compared with wheat endosperm (Rijven, 1986) or possible role of debranching enzymes in starch degradation (Nakamura et al, 1996) have been reported, ADP -glucose pyrophosphorylase and soluble starch synthase seem to be one of key enzymes under high-temperature stress. Further studies on the behavior of these enzymes are needed.…”
Section: Abbreviations On Figuresmentioning
confidence: 99%
“…Canopy temperature (Reynolds et al, 1994) Photosynthetic rate (Rijven, 1986) Chlorophyll content (Al-Khatib and Paulsen, 1984) Chlorophyll fluorescence (Azam et al, 2015) Stomata conductance (Reynolds et al, 1994) Stem reserve (Mohammadi et al, 2009) Membrane thermostability (Shanahan et al, 1990).…”
Section: Physiological Traitsmentioning
confidence: 99%